Rancang Bangun Sistem Penjualan berbasis Web (Studi Kasus CV. Adeeva Group - Jember) - Gilang Perdana; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Adeeva Group is dedicated to community economic empowerment. Adeeva Group was established not solely profit-oriented. But it is far more important than that, that business becomes a means (wasilah) for worship. Adeeva Group sells a variety of snacks, fashion and skincare that are produced in-house. There are various kinds of problems that are less effective and efficient in the process of recording goods because the system is still conventional using books. Problems also exist in sales transactions because the process is still done manually using personal chat social media, which makes sales transactions less efficient so that many consumers hesitate to buy products. The expense and stock books that are used as one to mark expenses are only colored with a highlighter so that sometimes when calculating expenses, they are not counted which causes calculation discrepancies. The method that can be used to reduce this problem is to develop a sales system that can solve the problem of online purchase and sales transactions, track the delivery of goods, record outgoing and incoming goods, and bookkeeping of stock items. This sales system is designed and built to help CV. Adeeva Group in solving the problems that occur. The system to be created will be web-based, so it must be able to work on a variety of web browsers. The following system development uses the waterfall development process model. Unit testing, integration, and validation have all been performed on the system below. Validation testing, integration testing, and unit testing all resulted in valid status on 6 test cases on unit testing, 3 test cases on integration testing, and 35 test cases on validation testing, respectively.